MENGEJAR PERINGKAT HDI*) NEGARA-NEGARA DI LINGKUNGAN ASEAN: BECHMARKING INDONESIA DAN VIETNAM - Ace Suryadi (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This article is to aim at scrutinizing factors that have explained the extent to which magnitude and rank of the Human Development Index of Indonesia had or had not improved in the last 8 year. Within this period, the Indonesia’s HDI has been consistently ranked at the 7th position after Vietnam’s, and Indonesia has won the race with this country only in 2004 and 2006. Nevertheless, Indonesia has a great potential to manage some measurable improvement through learning from other ASEAN countries’ experiences. Vietnam is the immediate choice for Indonesia to benchmark for the future HDI improvement. In the HDI 2007, Indonesia is already in favor in three out of the four indicators used to constitute the composite HDI, such as Literacy, Combine GER, and GDP per-capita, whereas Vietnam only is in the life expectancy. In the absence of weighting in the process of compositing the index, Indonesia has to accept the fact that its HDI is lower than that of Vietnam. In the future Indonesia needs being well organized and better coordination in managing HDI improvement affairs to make sure that the right data are timely collected and reported and the better policies on human development are implemented for more Jurnal Ekonomi dan Bisnis Indonesia, Vol 23 No.1,Januari 2008 effective human development programs.